Modelling of water droplets heat and mass transfer in the course of phase transitions. I. Phase transitions cycle peculiarities and iterative scheme of numerical research control and optimization - Miliauskas, Gintautas; Adomavičius, Arvydas; Maziukienė, Monika (Nonlinear Analysis: Modelling and Control, 2016)
The peculiarities of the widely applied in practice sprayed water droplets phase transition cycle are discussed in this article. Theoretical fundamentals of droplets heat and mass transfer modelling by combined analytical-numerical method and numerical simulation peculiarities are outlined. Water droplet phase transitions were modelled on the energy flow balance condition basis. The control mechanism of iterative scheme used to determine the droplet surface temperature was highlighted. The optimal finite number of members in the infinite integral equation set for droplet temperature field and its gradient parameter calculation was defined by the numerical experiment.
Keywords: water droplets; heat and mass transfer; Fourier time scale; phase transition cycle; numerical modelling; optimization and control